Molecular Fluorescence Imaging Spectroscopy for Mapping Low Concentrations of Red Lake Pigments: Van Gogh's Painting The Olive Orchard. (11th February 2020) - Dooley, Kathryn A.; Chieli, Annalisa; Romani, Aldo; Legrand, Stijn; Miliani, Costanza; Janssens, Koen; Delaney, John K.
Abstract: Vincent van Gogh used fugitive red lake pigments that have faded in some paintings. Mapping their distribution is key to understanding how his paintings have changed with time. While red lake pigments can be identified from microsamples, in situ identification and mapping remain challenging. This paper explores the ability of molecular fluorescence imaging spectroscopy to identify and, more importantly, map residual non‐degraded red lakes. The high sensitivity of this method enabled identification of the emission spectra of eosin (tetrabromine fluorescein) lake mixed with lead or zinc white at lower concentrations than elemental X‐ray fluorescence (XRF) spectroscopy used on account of bromine. The molecular fluorescence mapping of residual eosin and two carmine red lakes in van Gogh's The Olive Orchard is demonstrated and compared with XRF imaging spectroscopy. The red lakes are consistent with the composition of paint tubes known to have been used by van Gogh. Abstract : Auf der Suche nach Eosin : In‐situ‐Kartierung von flüchtigen roten Farbpigmenten (Eosin und Karmin) in einem Gemälde von van Gogh wurde mit bildgebender molekularer Fluoreszenzspektroskopie durchgeführt. Die hohe Empfindlichkeit dieser Methode ermöglichte es, niedrigere Konzentrationen von roten Pigmenten nachzuweisen als mit bildgebender elementarer Röntgenfluoreszenz‐Spektroskopie.